Biotechnological solutions for critical mineral recovery from unconventional feedstocks - Zurier, Hannah S; Banta, Scott; Park, Dan M; Reed, David W; Werner, Allison Z (Current opinion in biotechnology, 2025)
Secure and sustainable metal recovery from unconventional feedstocks is needed to meet the mineral demands of energy, defense, and electronic technologies. Here, we highlight the potential to leverage nature’s ability to extract and differentiate metal ions in biotechnologies that could become the next generation of mining and refining. We describe bulk and trace processes and then discuss the advances and opportunities of two key bioprocesses: microbially mediated solubilization of metal ions from solid matrices (termed ‘bioleaching’) and bio-based separation of solubilized ions via selective adsorption to proteins. Both biotechnologies have advantages such as reduced energy input for leaching low-grade feedstocks and reduced organic solvent demand for separating ions with similar physiochemical properties but require more development for industrial scale recovery from unconventional feedstocks. Innovation in biological science and engineering may bring timely solutions to key challenges toward recovering critical minerals from unconventional feedstocks. [Display omitted] •Microbes can catalyze reactions or produce chelators that solubilize metal ions (‘bioleaching’).•Proteins can selectively bind to metal ions, enabling aqueous metal separations.•Biotechnology advances could overcome key challenges towards critical mineral recovery.